Taxes and Infrastructure Development: A Review from Various Countries - Cahyadi, Rahadian (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This research examines the complex interactions between tax policy, infrastructure funding, and economic competitiveness, focusing on identifying the drivers and challenges in facilitating sustainable infrastructure development. Research Design and Methodology: The research systematically analyzed scholarly articles, books, and reports on taxation, infrastructure development, and public-private partnerships (PPPs). Keywords such as “tax policy,” “infrastructure funding,” “public-private partnerships,” “economic competitiveness,” and “sustainable development” were used to refine the search and ensure inclusiveness. Findings and Discussion: The results of this study demonstrate the critical role of taxation policy in mobilizing funds for infrastructure projects, the potential benefits and challenges of PPPs in addressing infrastructure deficits, and the implications of sustainable infrastructure development on long-term economic welfare. Implications: This research contributes to a deeper understanding of the complexities surrounding taxation, infrastructure development, and PPPs, ultimately informing more effective and sustainable approaches to infrastructure investment and governance.